Utilization of Fly Ash to Enhance Ground Waste Concrete-Based Geopolymer - Wu Chen; Zhiduo Zhu (Advances in Materials Science and Engineering)
Demolition of the deteriorating infrastructure produces a large amount of waste concrete. Storage of waste concrete involves costly transportation, consumption of limited landfill space, and serious environmental problems. Combining them, the recycling of waste concrete is mainly limited to the use of recycled aggregates in the nonstructural filler and base course. Considering the limited geopolymerization potential of waste concrete, this study investigates the feasibility of using fly ash to enhance ground waste concrete-based geopolymer to recycle and utilize waste concrete in high-specification applications. The unconfined compressive strength of the binders synthesized at different fly ash contents, NaOH concentrations, and curing time are evaluated. Scanning electron microscopy/energy dispersive spectroscopy imaging, X-ray diffraction analyses, Fourier Transform Infra Red analyses, and Magic Angle Spinning-Nuclear Magnetic Resonance Spectroscopy techniques are also conducted to investigate the microstructure and phase/elemental compositions of the synthesized geopolymeric binders. The results indicate that the addition of fly ash to ground waste concrete profoundly enhances the strength of ground waste concrete-based geopolymer up to 75% fly ash content. The simultaneous formation of geopolymeric gel and CSH gel is responsible for the strength increase. The geopolymeric binder with required strength can be produced by the appropriate addition of fly ash to ground waste concrete.